2017
DOI: 10.5423/ppj.nt.04.2017.0082
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Infection of Different Tomato Genotypes with Tomato mosaic virus Led to a Low Viral Population Heterogeneity in the Capsid Protein Encoding Region

Abstract: The complete genome sequence of a Slovak SL-1 isolate of Tomato mosaic virus (ToMV) was determined from the next generation sequencing (NGS) data, further confirming a limited sequence divergence in this tobamovirus species. Tomato genotypes Monalbo, Mobaci and Moperou, respectively carrying the susceptible tm-2 allele or the Tm-1 and Tm-2 resistant alleles, were tested for their susceptibility to ToMV SL-1. Although the three tomato genotypes accumulated ToMV SL-1 to similar amounts as judged by semi-quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…After reverse transcription, the cDNA was amplified using primers specific for ToMV SL-1 coat-protein-coding sequences (CP1 and CP2) and primer pairs P1-P6. The obtained amplicons had the expected size and the Sanger sequencing analysis revealed 100% sequence homology with the previously sequenced ToMV SL-1 isolate [29] in both plants.…”
Section: Identity Of Tomv Sl-1 Isolatementioning
confidence: 62%
See 3 more Smart Citations
“…After reverse transcription, the cDNA was amplified using primers specific for ToMV SL-1 coat-protein-coding sequences (CP1 and CP2) and primer pairs P1-P6. The obtained amplicons had the expected size and the Sanger sequencing analysis revealed 100% sequence homology with the previously sequenced ToMV SL-1 isolate [29] in both plants.…”
Section: Identity Of Tomv Sl-1 Isolatementioning
confidence: 62%
“…The virus originated from a tomato plant manifesting symptoms of virus infection at a local tomato grower in Western Slovakia. Leaves from this plant were collected and stored at −80 • C. The nucleotide sequence of the complete genome of the ToMV SL-1 isolate was determined previously by high-throughput sequencing [29] and included in the GenBank nucleotide database (KY912162, available at: https://www.ncbi.nlm.nih.gov/nucleotide/, accessed on 27 May 2022). This analysis showed that the source tomato plant was infected solely by ToMV without co-infection with other viruses.…”
Section: Tomv Sl-1 Isolate and Tomato Genotypesmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar method as reported in ref was used to treat the tomato leaves with tomato ringspot virus (ToRSV) and prepare the leaf samples. The ToRSV inoculation buffer was obtained from Institute of Virology, Biomedical Research Center of Slovak Academy of Sciences (store at −20 °C) . The lower leaves of the tomato plants with an age of 5 weeks were inoculated by ToRSV.…”
Section: Methodsmentioning
confidence: 99%